COMMUNICATION AND INTERDISCIPLINARY TEAM WORK IN PALLIATIVE CARE - Maués de Souza, Fernando; Evandro Leão, Rômulo; de Nazaré Baía Siqueira, Janides (Health and Society, 2022)
Palliative care is a treatment modality that aims to improve the quality of life of patients and their families. Communication and interdisciplinary relationships are significant elements in the palliative care process. The present study aims to point out the importance of interdisciplinary communication, based on the approach of different authors, in the, care of patients in palliative care. This is an exploratory research, having as a tool the bibliographic review of authors who discuss the subject. In this study, the importance of communication in interdisciplinary teamwork in the team, patient and family relationship is verified.